Effects of Compensation Measures on Post-earthquake Building Reconstruction by Taking Reconstruction Factors as Mediating Variables: Evidence from China - Quan Mao; Junhan Du; Yile Wu; Jaynax Tasken; Yulong Li (International Journal of Disaster Risk Science)
Abstract Post-earthquake building reconstruction usually faces challenges such as inadequate preparation and lack of resources, while compensation measures can help alleviate these difficulties. Although various compensation measures have been proposed for accelerating post-earthquake recovery, their effects on building reconstruction are still unclear. This study aimed to analyze and evaluate the effects of compensation measures on post-earthquake building reconstruction. To achieve this objective, this study first identified the post-earthquake building reconstruction goals, 21 reconstruction factors across five categories, and four compensation measures, and employed the methods of structural equation modeling, paired-samples t-test, and repeated measures analysis of variance to analyze the effects of reconstruction factors on the reconstruction goals and the effects of compensation measures on the reconstruction factors, respectively. A questionnaire was designed to investigate the post-earthquake building reconstruction projects in China, with 251 respondents participated. The results show that apart from project-specific condition, the other four categories of reconstruction factors, including owner condition, technology condition, resource availability, and contractor management capability, have significant effects on the reconstruction goals. The study also evaluated the extent of the above effects. On the other hand, the results indicate that the affecting extents of various compensation measures on reconstruction factors are significantly different. These findings can provide support and guidance for government management of post-earthquake building reconstruction and the development of compensation measures. They also provide a basis for future research on optimizing compensation measures for post-earthquake building reconstruction.